DESIGN AND ANALYSIS OF A MULTIPOINT TEMPERATURE DATALOGGER (Nigerian Journal of Technology, 2016)
In this work, a low cost six- multipoint temperature data logger was developed. It was designed using LM35 as the sensor, and arduino Uno as the data processing element. The response time of the sensor was observed to be between three and four minutes. The comparative evaluation of the system with other established thermometers show that no two temperature meters gave the same values. However the most important thing is that all the systems recorded the same temperature flow pattern. This indicates that the systems actually senses change in the surrounding effectively. In relation to the alcohol thermometer, the designed system shows an accuracy of +0.4oC at temperatures below 300C and +1.850C at temperatures above 300C. The system gives room for effective and adjustable temperature data logging procedure. Hence, the system is recommended for use in monitoring low temperature systems. http://dx.doi.org/10.4314/njt.v35i2.30